Surface Engineering of Silicon Quantum Dots: Does the Ligand Length Impact the Optoelectronic Properties of Light‐Emitting Diodes?. Issue 9 (16th July 2021) - Mock, Josef; Groß, Elisabeth; Kloberg, Marc Julian; Rieger, Bernhard; Becherer, Markus
Abstract : Herein, silicon quantum dot light‐emitting diodes (SiQD LEDs) are investigated to explore the interplay between their electroluminescence (EL) blue shift and the SiQD ligand length on the SiQD surface. The ligand is essential for LED fabrication to ensure colloidal stability, but it also hinders efficient charge transport inside the LED. Consequently, the SiQDs are functionalized via organolithium reagents with hexyl, octyl, and dodecyl to obtain a low‐SiQD surface coverage and therefore improved charge transport. With increasing ligand length, the potential barrier between the SiQDs increases, which is ideal for charge carrier confinement, but a trade‐off with the charge transport has to be found. A sweet spot for LED performance is found for octyl‐functionalized SiQDs with the highest irradiance (734 μW cm −2 ) and external quantum efficiency (1.48%), compared with shorter hexyl‐ and longer dodecyl‐capped SiQDs. The SiQDs exhibit a size distribution, whereas the bandgap energy of SiQDs is inversely proportional to the SiQD size. Therefore, large SiQDs with a short ligand are accessible at low voltages, whereas small SiQDs with long ligands require elevated voltages. This leads to a broadening and a blue shift of the EL spectrum and a ligand length‐controlled size‐selective SiQD activation. Abstract : The ligand length on silicon quantum dots (QDs) is varied and the optoelectronic performance of light‐emitting diodes (LED) is investigated. The ligand reduces charge transport between the QDs, which affects the LED performance, but it enables to tune the full width at half maximum and the blue shift of the electroluminescence spectra due to the size distribution of the QDs.